Emerging adulthood, sharing utilities and intention to use sharing services. Issue 2 (9th April 2018) - Oyedele, Adesegun; Simpson, Penny
Abstract : Purpose: This study aims to testLamberton and Rose's (2012 ) commercial sharing utility model of access-based consumption use in three different contexts: car-sharing, room-sharing and household goods purchases. More importantly, this research extends the model by examining the effects of emerging adulthood as a life-stage on perceived value of social applications that facilitate and promote transaction utility, called shareaids. Design/methodology/approach: A questionnaire designed to evaluate the effects of emerging adulthood and sharing utilities on intention to use sharing services was developed and administered to 345 respondents at a Midwestern US university. The data were analyzed using partial least squares structural equation modeling. Findings: Results indicate that flexibility utility had the strongest direct impact on intention to use sharing consumption while also having indirect effects in all contexts examined. The emerging adulthood life-stage was found to affect transaction utility and shareaids as predicted, and shareaids positively influenced consumers' perception of the social utility value of access-based consumption. Research limitations/implications: The generalizability of this study is limited by its use of a student sample. Also, the study suffers from inherent limitations linked to self-reported survey research. Practical implications: Sharing services that have a strong social component could use shareaids to gain a competitive advantage. Examples of shareaid application include split bills for multiple payments to split fares among friends and social media transaction tools. Shareaid applications can enhance consumers' perception of social value and the overall shareability value of the sharing service. Originality/value: This is the first known study to test the effects of emerging adulthood as a life-stage on perceived value of social applications that facilitate and promote transaction utility, called shareaids.